Defining the Unemployment Determinants of the Post-Transition Central European EU Member Countries - Marija Buselic; Jurica Bosna (Managing Global Transitions, 2019)
Aim of the research is to define unemployment determinants of the labor markets on the example of post-transition Central European eu member countries – Poland, Czech, Slovak, Hungary, Slovenia, and Croatia. The purpose of the paper is to point out the role and importance of studying the labor market unemployment determinants of the post-transition countries to provide a proposal for reducing unemployment. In this paper as independent macroeconomic variables have been analyzed gross domestic product, public debt, labor force participation rate and institutional variables like some fixed-term and part-time contracts and expenditures for active and passive labor market policies.An analysis of the labor market unemployment determinants for the Central European eu member countries has been conducted by econometric models of multiple linear regression for each country to determine whether there are differences in unemployment rates between countries within one panel. Results of the research show that in almost all countries, public debt as a macroeconomic variable has a significant impact on unemployment growth, while passive labor market policies of the institutional variables have the most significant impact on the level of unemployment.